The Plant Family Asteraceae Is a Cache for Novel Fungal Diversity: Novel Species and Genera With Remarkable Ascospores in Leptosphaeriaceae - Doilom, Mingkwan; Hyde, Kevin D.; Dong, Wei; Liao, Chun-Fang; Suwannarach, Nakarin; Lumyong, Saisamorn (Frontiers in Microbiology, 2021)
The plant family Asteraceae is proving to be a cache of novel fungal species with a recent study on Siam weed yielding 47 new species. In a cursory survey of fungi on Asteraceae in Yunnan Province, China we have collected ten taxa, many of which may be novel species. In this paper, we report on species that belong to the family Leptosphaeriaceae (Pleosporales, Dothideomycetes). Two novel species have remarkable ascospores that are unusual for sexual ascomycetes. Multilocus phylogeny of LSU, SSU and ITS sequence data showed one to be novel genus, while the other is a new species. Praeclarispora artemisiae gen. et sp. nov. is introduced and is typical of Leptosphaeriaceae, but has unusual fusiform, hyaline ascospores with a brown median cell. Sphaerellopsis artemisiae sp. nov. has scolecosporous ascospores with deeply constricted septa that split into two parts, which resembles to S. isthmospora, but differs by ascospore dimension and molecular data. In addition, Plenodomus artemisiae is reported as a new collection from dead stems of Artemisia argyi in Qujing City. Plenodomus sinensis is reported as a new host record from Ageratina adenophora. All taxa are illustrated and described based on evidence of taxonomy and phylogeny. We provide protein-coding gene (TEF) for our strains to facilitate the future identification of species, but it is not used in the combined phylogenetic analysis as most species of Leptosphaeriaceae lack TEF sequence data, and some known species were sequenced using different primer pairs.